Quad-Band 3D Rectenna Array for Ambient RF Energy Harvesting - Fatima Khalid; Warda Saeed; Nosherwan Shoaib; Muhammad U. Khan; Hammad M. Cheema (International Journal of Antennas and Propagation)
This paper presents a quad-band, 3D mountable rectenna module for ambient energy harvesting. With the aim of powering up Internet of Things (IoT) nodes in practical ambient environments, a hybrid approach of combining power, both at RF and DC, is adopted using 98 MHz FM band, GSM900 (Global System for Mobile Communications), GSM1800, and Wi-Fi 2.4 GHz band. A dual polarized cross-dipole antenna featuring asymmetric slots as well as central ring structure enables multiband response and improved matching at the higher three frequency bands, whereas a loaded monopole wire antenna is used at the lower FM band. Four identical multiband antennas are placed in a 3D cubic arrangement that houses a 4-to-1 power combiner and matching circuits on the inside and the FM antenna on the top. In order to maintain stable rectenna output at varying input power levels and load resistances, a novel transmission line based matching network using closed form equations is proposed. Integrated in form of a 10 × 10 × 10 cm3 cube using standard FR4 substrate, the rectenna generates a peak output voltage of 2.38 V at −10 dBm input power. The RF to DC conversion efficiency is 70.28%, 41.7%, 33.37%, and 27.69% at 98 MHz, 0.9 GHz, 1.8 GHz, and 2.4 GHz, respectively, at −6 dBm. The rectenna also exhibits a measured conversion efficiency of 31.3% at −15 dBm for multitone inputs in ambient environment. The promising results in both indoor and outdoor settings are suitable to power low power IoT devices.